Investigating the regulation of ZUP1, a novel deubiquitinating enzyme involved in DNA repair, by coupled monoubiquitination - Schützenhofer, K (2021)
Ubiquitination, a major post-translational modification, is reversed through the action of a large family of specialised proteases termed deubiquitinating enzymes (DUBs). Due to their involvement in key cellular pathways, such as inflammation, the cell cycle and DNA repair, as well as their potential as targets for therapeutic intervention, DUBs are critical to investigate. ZUP1 is a recently discovered DUB with cleavage specificity for lysine-63 conjugated polyubiquitin chains and has been proposed to have a role in DNA repair and genome stability maintenance via deubiquitination of the Replication Protein A complex. The regulation of DUBs is not well understood, but it has been suggested that ZUP1 undergoes a modification termed coupled monoubiquitination. Coupled monoubiquitination is a process whereby ubiquitin-binding proteins are monoubiquitinated themselves, which effectively abolishes their ubiquitin binding in trans, providing an inhibitory control mechanism. Here, by mutating two of the ubiquitin-binding domains of ZUP1, I show that ZUP1 monoubiquitination is dependent on the integrity of its ubiquitin binding domains, indicating that ZUP1 undergoes coupled monoubiquitination. Moreover, loss of monoubiquitination leads to a reduction in binding to another deubiquitinating enzyme involved in DNA repair, USP11 and its binding partner TCEAL1, an as of yet uncharacterised DNA repair protein. Together, I provide evidence that ZUP1 is regulated by coupled monoubiquitination which sets the foundation to further dissect the functional importance of this regulation in cells and to its enzymatic activity.